Potencial de produção de metano de bovinos submetidos à dieta suplementada com resíduo úmido de cervejaria - Mallmann, Larissa Schmatz (2013)
Livestock, especially cattle, has been considered one of the main sectors that is responsible for global warming due to rumen methane emission and, to a lesser extent, methane emission by residues. Another concern is the correct disposal of agroindustrial residues. The wet brewery grain is considered as polluting as animal wastes. Thus, such wastes must have correct destination, so their use to feed animal is an option. The wet brewery grain has been recorded as an important substitute for fodder and/or grain in ruminants diet. Thus, this study aimed at evaluating the potential for methane production in cattle fed diets containing different levels of wet brewery grain inclusion, to replace bulky diet, with 0, 20, 25 and 30% rates in dry matter percentage. Four castrated steers, with rumen cannula were studied and distributed in a Latin square design (4x4) in four experimental periods of 21 days each (14 days of adjustment and 7 days for data collection). During the last week of each period, the animals manure and ruminal fluid were collected, whose anaerobic digestion essays were analyzed, during the period of 120 days. So, the following parameters were evaluated: removal of total and volatile solids, removal of soluble chemical oxygen demand, cumulative and daily production of methane, volatile fatty acids production (lactic, acetic, propionic and butyric), acidity/alkalinity ratio and pH of reactors. In order to record ruminal fluid, 96-hour tests were performed in the laboratory to observe the influence of wet brewery grain inclusion on methane and volatile fatty acids production inside the rumen. The statistical evaluation of the process was obtained with curves of cumulative production of methane that were adjusted according to Gompertz modified model. Tukey test was used to compare averages with 5% significance. According to these data, it is concluded that wet brewery grain inclusion influenced on methane production for these animals. There was effect of treatment and period for cumulative production of methane (L). The treatment with the largest inclusion of wet brewery residue showed the highest potential of methane production in wastes. The wet brewery residue inclusion did not affect the production of volatile fatty acids inside rumen. The cumulative methane production (mL) of ruminal fluid was influenced by the inclusion of wet brewery residue on animals diet. Nevertheless, the lowest production occurred with an increasing supply of wet brewery residue. The Gompertz modified model provided a good adjustment to the methane production data. Consequently, wet brewery residue can be considered an alternative diet to replace corn silage up to 30% (DM), since it reduces methane production inside the rumen (environmental benefit) and increases methane production from residues (energy and economic benefit).